the hardy boys mystery stories 49 : the bombay boomerang - Franklin W. Dixon; Franklin W. Dixon (New York Grosset & Dunlap, 1970)
In The Hardy Boys #49: The Bombay Boomerang, Frank and Joe Hardy investigate a national security threat involving stolen mercury and a missing "Super S" missile, triggered by a wrong-number phone call mentioning "Bombay Boomerang". The brothers, along with their father Fenton, race against time to stop a smuggling ring.
English